Design vany pro porod do vody - Navrátilová, Sára (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2019)
Tématem diplomové práce je design vany pro porod do vody. Za cíl si klade zlepšení tvarových, ergonomických a bezpečnostních parametrů ve srovnání se současnými zástupci. Výsledný návrh je nový produkt, který je vhodný pro profesionální medicínské prostředí a zároveň odráží psychologické aspekty porodu.

The topic of this diploma thesis is a design of bathtub for delivery to water. The goal is to improve shape, ergonomic and safety parameters compared to current representatives. The resulting design is a new product that is suitable for the professional medical environment while reflecting the psychological aspects of childbirth.
Design of Waterbirth Vessel
Keywords: Design; Vana; Vana pro porod do vody; Porod do vody; Design; Bath; Waterbirth wessel; Water birth